NYAI DASIMA AND THE PROBLEM OF INTERPRETATION : INTERTEXTUALITY, RECEPTION THEORY, AND NEW HISTORICISM - Umar Junus (Humaniora, 1999)
Due to the prevalent concept of literature being a document, recording an incident, as well as the lack of proper historical documents, people tend to take for granted that the description of a society in a literary work as an authentic description of the society it describes . Sejarah Melayu "Malay Annals is then simply regarded as an authentic description of the Malay society in the Sultanate of Malacca . They never bother to questioning it although they know it was written more than 100 years after the fall of the Sultanate - for a further discussion please refer to Umar Junus, 1984 and Cheah Boon Kheng, 1998 . Accordingly, one might take the same attitude towards Cerita Njai Dasima "Nyai Dasima story" by G. Francis (1896) which relates an incident in 1813 . In this case, I agree with Kenji Tsuchiya (1991 :476) who reminds us about the time difference between the incident and the time the work, which reported it, was written and published which does not allow us to take it as an authentic description of the respective incident. It is quite possible that the incident did take place in 1813